INTRODUCTION TO DIFFERENTIAL EQUATIONS FOR ENGINEERING STUDENTS - MANSHOOR, BUKHARI; HARIRI, AZIAN; SALLEH, HAMIDON (Penerbit UTHM, 2021)
This book is written based on the teaching experience and the lecture notes of the authors at Universiti Tun Hussein Onn Malaysia, Malaysia and Telkom University, Indonesia, for more than 15 years. The chapters in this book are designed to cover the syllabus for the course of differential equations, which is one of the compulsary mathematics courses for most of the engineering programme in university. This book consists of six chapters, included Chapter 0: short Mathematical Revision, which is an introduction and a brief revision on basic mathematic that required for the fundamental differential equations. The contents start with the basic concept of ordinary differential equations (ODEs), which is the most immediately useful part of the calculus. The next chapters followed by the first and second order of ODEs with constant coefficient, Laplace transforms, Fourier series and ended with an introduction to partial differential equations.